Resonant enhancement of polymer-cell optostimulation by a plasmonic metasurface - Maity, Arijit (2023)
Organic semiconductors have shown great potential as efficient bioelectronic materials. Specifically, photovoltaic polymers such as the workhorse poly(thiophene) derivatives, when stimulated with visible light, can depolarize neurons and generate action potentials, an effect that has been also employed for rescuing vision in blind rats. In this context, however, the coupling of such materials with optically resonant structures to enhance those photodriven biological effects is still in its infancy. Here, we employ the optical coupling between a nanostructured metasurface and poly(3-hexylthiophene) (P3HT) to improve the bioelectronic effects occurring upon photostimulation at the abiotic-biotic interface. In particular, we designed a spectrally tuned aluminum metasurface that can resonate with P3HT, hence augmenting the effective field experienced by the polymer. In turn, this leads to an 8-fold increase in invoked inward current in cells. This enhanced activation strategy could be useful to increase the effectiveness of P3HT-based prosthetic implants for degenerative retinal disorders.